2012
DOI: 10.1007/s11524-011-9654-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mindfulness-Based Intervention Program to Decrease Blood Pressure in Low-Income African-American Older Adults

Abstract: Hypertension affects a large proportion of urban African-American older adults. While there have been great strides in drug development, many older adults do not have access to such medicines or do not take them. Mindfulness-based stress reduction (MBSR) has been shown to decrease blood pressure in some populations. This has not been tested in low-income, urban African-American older adults. Therefore, the primary purpose of this pilot study was to test the feasibility and acceptability of a mindfulness-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
95
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 24 publications
1
95
1
1
Order By: Relevance
“…Teixeira (2010) instructed participants in mindfulness meditation and encouraged them to listen to a guided CD 5 days/week for 4 weeks, but did not include other elements of the MBSR curriculum. Palta and colleagues (2012) used an 8-week MBSR program with shortened weekly sessions called ELDERSHINE (developed and implemented by an interventionist trained through the Center for Mindfulness—University of Massachusetts), consisting of meditation practice, homework review, and didactic training of mindfulness skills to improve social and emotional functioning. Mularski et al (2009) utilized a standard 8-week MBSR program with supplemental relaxation and mindful breathing training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Teixeira (2010) instructed participants in mindfulness meditation and encouraged them to listen to a guided CD 5 days/week for 4 weeks, but did not include other elements of the MBSR curriculum. Palta and colleagues (2012) used an 8-week MBSR program with shortened weekly sessions called ELDERSHINE (developed and implemented by an interventionist trained through the Center for Mindfulness—University of Massachusetts), consisting of meditation practice, homework review, and didactic training of mindfulness skills to improve social and emotional functioning. Mularski et al (2009) utilized a standard 8-week MBSR program with supplemental relaxation and mindful breathing training.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies did not provide attendance data; however, those that did reported that participants attended an average of 6-8 of the 8 sessions (Creswell et al 2012; Morone et al, 2008; Splevins et al, 2009). Palta et al (2012) reported that greater than 80% of their participants completed all eight sessions. In a nursing home setting, 75% of participants completed all sessions (Ernst et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, most MBIs with older adults studies involve clinical populations, with either mental disorders like depression (Lynch & Bronner, 2006) or physical issues like back pain (Morone et al, 2008). There are exceptions that focus on community populations, but these generally still utilise interventions developed for clinical groups (e.g., MBSR), and are focused on correcting deficits, such as reducing emotional distress (Young & Baime, 2010) or blood pressure (Palta et al, 2012). Morone et al's (2009) mind-body intervention does appear to be designed specifically for older community-dwelling adults, but again, is still somewhat 'deficit focused,' with a homework book entitled 'Keep your brain alive.'…”
mentioning
confidence: 99%